2019
DOI: 10.1042/bsr20181440
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAS8-AS1 suppresses papillary thyroid carcinoma cell growth through the miR-135b-5p/CCND2 axis

Abstract: The aim of the present study was to investigate the potential role of GAS8 antisense RNA 1 (GAS8-AS1) in papillary thyroid carcinoma (PTC). PcDNA3.1-GAS8-AS1 and si-GAS8-AS1, miR-135b-5p mimic and si-CCND2 were transfected into PTC cells. Cell proliferation was evaluated by Cell Counting Kit-8 (CCK-8). QRT-PCR was used to determine expressions of GAS8-AS1, miR-135b-5p, and CCND2, and Western blot were detected protein level of CCND2. The miRNA target gene prediction site TargetScan was used to predict potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…From the same families of genes discovered to be the target of several microRNAs we mention CXCL-12/16 [16,86], CCNG-1/2 [17,100], IRS-1/2 [19,107], FGF-2/FR [28,112], CCDC-6/67 [52,128], FOX-O1/E1/M1 [27,55,76], ITGA-3/6 [55,61], SL-1A5/25A1 [56,118], MAP-2K4/K1/4K3 [71,78,120], and SOX 11/12/2 [84,95,117].…”
Section: One Gene Can Be Targeted By Several Micrornasmentioning
confidence: 99%
“…From the same families of genes discovered to be the target of several microRNAs we mention CXCL-12/16 [16,86], CCNG-1/2 [17,100], IRS-1/2 [19,107], FGF-2/FR [28,112], CCDC-6/67 [52,128], FOX-O1/E1/M1 [27,55,76], ITGA-3/6 [55,61], SL-1A5/25A1 [56,118], MAP-2K4/K1/4K3 [71,78,120], and SOX 11/12/2 [84,95,117].…”
Section: One Gene Can Be Targeted By Several Micrornasmentioning
confidence: 99%
“…The differential expressions of those lncRNAs have also been found to be cells, tissue, and plasma in the TC. As discussed earlier, some lncRNAs, such as CCAT1, H19, HCP5, HOTTIP, , MALAT1, HOXA-AS2, SNHG15, SPRY4-IT, and UCA1, have been found to be upregulated in TC (7,23,25,26,30,42,70,111,112), whereas others, such as BANCR, AB074169, ASMTL-AS1, BLACAT1, CASC2, HOTAIRM1, GAS5, PAR5, SNHG3, GAS8-AS1, and MEG3 are downregulated (38)(39)(40)(43)(44)(45)47,104,108,112,113). This unique biologic behavior exhibited by different groups of lncRNAs shows value for the prognostic and diagnostic determination in TC patients.…”
Section: Lncrnas As Diagnostic and Prognostic Markers In Tcmentioning
confidence: 74%
“…Chen et al found that the GAS8-AS1 was downregulated in PTC cell lines and suppressed the cell proliferation and cycle of PTC cells. Further studies showed that GAS8-AS1 regulates a downstream target of miR-135b-5p, cyclin G2, whereas overexpressed GAS8-AS1 inhibits tumor formation and suppresses PTC cell growth (108). These studies demonstrate that GAS8-AS1 inhibits PTC cell growth via the miR-135b-5p/CCND2 axis, and acts as a tumor suppressor gene in PTC.…”
Section: Gas8-as1mentioning
confidence: 76%
“…And then MLK7-AS1 upregulated the expression of Yes related protein 1, promoted the proliferation and development of OC, and was associated with the survival and prognosis of OC patients. 10 It has been reported that GAS8-AS1 contributed to the development of colorectal cancer, 11 papillary thyroid carcinoma 12 and hepatocellular carcinoma. 13 However, the function of GAS8-AS1 in ovarian cancer is poorly defined.…”
Section: Introductionmentioning
confidence: 99%